2023
DOI: 10.1108/jap-01-2023-0001
|View full text |Cite
|
Sign up to set email alerts
|

Moral intuitions, social skills and elder abuse: exploring a social exchange hypothesis

Abstract: Purpose This study aims to operationalize and test some predictions of a social exchange theory of elder abuse. The theory proposes that the combination of low resources and high dependency/low relational power increases the older adult’s risk of abuse. The authors tested these predictions by exploring the association between morality (indicator of resources) and abuse, moderated by social skills (indicator of power). Design/methodology/approach This was an exploratory study. The authors collected data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…In their study, Metlife and partners (2009) revealed that in instances of EFA, close relatives, particularly sons, are 2.5 times more likely to be implicated. Our findings align with those of Fundinho and Ferreira-Alves (2023), who examined social exchange in the context of moral intuitions and elder abuse. We observed that strong moral convictions and cultural beliefs can, in certain situations, have unintended consequences for older adults.…”
Section: Discussion Implications and Conclusionsupporting
confidence: 88%
See 1 more Smart Citation
“…In their study, Metlife and partners (2009) revealed that in instances of EFA, close relatives, particularly sons, are 2.5 times more likely to be implicated. Our findings align with those of Fundinho and Ferreira-Alves (2023), who examined social exchange in the context of moral intuitions and elder abuse. We observed that strong moral convictions and cultural beliefs can, in certain situations, have unintended consequences for older adults.…”
Section: Discussion Implications and Conclusionsupporting
confidence: 88%
“…This vulnerability could be exacerbated by a potential rise in individualism and materialistic values among younger British Pakistanis. Multiple studies have supported and confirmed elder financial abuse (EFA) by family members (Fundinho and Ferreira-Alves, 2023; Bagshaw et al , 2013; Metlife. 2009).…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%